Determinative characteristics of modern social reality in the formation of the value image of the teaching profession among young people - S. Bobryshov; L. Sumenko; Ju. Katylevskaya (Вестник Северо-Кавказского федерального университета)
In pedagogical education, the problem of the formation of students’ value attitude to the pedagogical profession and the personality of the teacher was actualized. This is determined by a contradictory situation in which, on the one hand, future teachers are required to demonstrate a number of professionally significant humanistically oriented moral qualities, abilities and skills, and, on the other hand, young people in modern society, even before entering university, form views and personal qualities that are in many ways the opposite of what is required. As a result, the meanings of education, pedagogical activity and the teaching profession in general are significantly distorted, which acts as a barrier to students mastering pedagogical knowledge and technologies.   The aim of the work was to identify the key characteristics of modern social reality that determine the perception of the value image of the teaching profession by young people.   Based on the predicative-semantic approach, the essential-semantic, structural-meaningful and functional understanding of the phenomenon of sociality of the teacher and the pedagogical profession is presented. The social effects derived from transformational and modernization processes in the life of society that load the consciousness of young people with negative life meanings are revealed and disclosed. It is shown that these meanings form negative value orientations in young people that contradict the essence of the pedagogical profession, pedagogical activity and the image of a teacher.